Effective algebraic geometry and normal forms of reversible mappings - Jacquemard, A.; Teixeira, M.A. (Revista Matemática Complutense, 2002)
We present a new method to compute normal forms, applied to the germs of reversible mappings. We translate the classification problem of these germs to the theory of ideals in the space of the coefficients of their jets. Integral factorization coupled with Gr¨obner basis construction is the key factor that makes the process efficient. We also show that a language with typed objects like AXIOM is very convenient to solve these kinds of problems.